Intraarticular use of tranexamic acid reduces blood loss and transfusion rate after primary total knee arthroplasty - Eric Tille; Jonas Mysliwietz; Franziska Beyer; Anne Postler; Jörg Lützner (BMC Musculoskeletal Disorders, 2019)
Abstract Background Tranexamic acid (TXA) is effective in reduction of hemorrhage after major surgical procedures. In total joint replacement it is commonly administered intravenously. Despite various studies regarding the safety of its antifibrinolytic effect there are contraindications for systemic use. In total knee arthroplasty (TKA) TXA can also be administered intraarticular. However, there is a lack of studies focusing on dosage, effectiveness and complications of this local treatment. This study aimed to evaluate if blood loss and transfusion rate can be reduced in primary TKA by local application of TXA. Methods We included a total of 202 consecutive primary, unilateral TKA patients, 101 without and 101 with intraartricular application of 2 g TXA. Surgery was conducted after a standardized protocol. Blood loss, transfusion and complication rates were evaluated until three months after surgery. Blood loss was estimated using the hematocrit-value (Hk) prior and five days after surgery by Rosenecher’s and Mercuriali’s formula. Results By the use of TXA a significant reduction of blood loss (Rosencher average 1220 ml vs 1900 ml, Mercuriali average 430 ml vs 700 ml p < 0,001) and transfusion rate (0% vs 24.75% of patients, p < 0,001) was observed. There were no differences regarding complication rates. Due to the lower cost of TXA compared to applied erythrocyte concentrates a side effect of the treatment was a cost reduction of € 1.609 within this cohort. Conclusions The intraarticular application of 2 g TXA resulted in a significant reduction of blood loss and transfusion rate after primary TKA without increased complication rates. This method therefore seems to be a safe and cost effective instrument to reduce perioperative blood loss. However, it has to be considered that this is an off-label use.